2017
DOI: 10.1177/0898264317713135
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Spouse Support Among Older Couples Living With Sensory Loss

Abstract: The findings highlight the need to support the mental health of couples living with sensory loss and indicate the importance of considering the intimate relationship in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
(54 reference statements)
1
17
1
2
Order By: Relevance
“…It is noteworthy that these similar results come from two studies that used different measures of depression. Our finding on depression contradicts several other studies that found: no differences between DSL and single sensory impairment [35,36], worse results for DSL when compared to both VL and HL [38][39][40][41], and worse results for DSL only when compared to HL [37,42]. There are several differences between these prior studies and ours which may account for the mixed findings including diverse measures of sensory impairment and depression, and sample's age range.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that these similar results come from two studies that used different measures of depression. Our finding on depression contradicts several other studies that found: no differences between DSL and single sensory impairment [35,36], worse results for DSL when compared to both VL and HL [38][39][40][41], and worse results for DSL only when compared to HL [37,42]. There are several differences between these prior studies and ours which may account for the mixed findings including diverse measures of sensory impairment and depression, and sample's age range.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings suggest that older adults with DSL would have worst levels of depression than those with single sensory impairment. However, results on this topic are mixed and cross-sectional studies report diverse patterns: no differences in number of depressive symptoms [ 35 ] or major depression [ 36 ] when comparing older adults with DSL versus single sensory impairment; DSL is associated with a higher likelihood of symptoms of depression compared to HL (but not VL) [ 37 ]; DSL is associated with a greater chance or rate of depression compared to HL and VL [ 38 40 ]. Findings from longitudinal research are also inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that couples living with sensory loss are at risk for relational and psychological distress (Lehane, Hofsöe, Wittich, & Dammeyer, ; Strawbridge, Wallhagen, & Shema, ; Wallhagen, Strawbridge, Shema, & Kaplan, ). Although acceptance of the sensory loss has been identified as protective against distress among AWSLs, the value of acceptance within intimate relationships or for the well‐being of significant others was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Since the review on DSL and mental health was published by Heine and Browning (19), some new studies have appeared. For example, based on cross-sectional data of 8,500 adults aged 50 years and older from Wave 1 of the Irish Longitudinal Study on Aging (TILDA), collected between 2009 and 2011, Lehane et al (23) found that the loss of one's own or one's spouse's hearing and/or vision is a stressful experience. Furthermore, individuals with DSL reported greater levels of both anxiety and depression, whilst their spouses reported greater levels of depression only when compared to couples without sensory loss.…”
Section: Introductionmentioning
confidence: 99%